Implementation of Higher Order Thinking Skills Learning - Palangda, Listriyanti; Abu, Ilham; Watung, Sjeddie Rianne; Chintya, Julien (International Journal of Multi Discipline Science (IJ-MDS), 2025)
This study aims to describe the implementation of Higher Order Thinking Skills (HOTS)-based learning at SMP 8 Satu Atap (SATAP) Tondano, particularly in core subjects such as Mathematics, Science, and Indonesian Language. HOTS-based learning is essential to equip students with critical thinking, creativity, and the ability to solve complex problems in line with the demands of the Merdeka Curriculum and the Industrial Revolution 4.0. This study employed a qualitative approach using a case study method. The subjects used in this study were 5 teachers. Data collection techniques included in-depth interviews with teachers. The results of the study indicated that teachers had made efforts to integrate HOTS elements into the learning process through the use of trigger questions, group discussions, and project-based assignments. However, the implementation still faced various obstacles, such as limited infrastructure, low student learning motivation, and a lack of teacher training in HOTS lesson planning. To overcome these challenges, teachers applied strategies such as scaffolding, the use of contextual learning media, and collaboration among teachers. This study concluded that the implementation of HOTS-based learning at SMP 8 SATAP Tondano was underway but not yet optimal, and still required strengthened institutional support and teacher capacity building.